On God - "Krishnamurti, J" (Hampshire, 2004)
On God is one of a series of theme books put together from the talks and writings of J. Krishnamurti. The book contemplates our search for the sacred. 'Sometimes you think life is mechanical, and at other times when there is sorrow and confusion, you revert to faith, looking to a supreme being for guidance and help.' Krishnamurti explores fully the futility of seeking knowledge of the 'unknowable' and shows that it is only when we have ceased seeking with our intellects that we may be 'radically free' to experience Reality, Truth, or bliss. He presents the 'religious mind' as one that directly perceives the sacred rather than adhering to religious dogma.
Keywords: Religion